MAINTAINING THE SELF-EXISTENCE THROUGH SHORT STORY â€œJALAN SUMUR MATIâ€ - Wahyuni, Dessy; Maulina, Yeni (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
Riau is a wealthy region where physical development appears everywhere. However, many people are marginalized and neglected by this development. Due to this fact, most Riau Malay people tend to have negative prejudice and not accept the presence of foreign immigrants, including Indonesian Chinese. However, Olyrinson can blend in with the local community through his work, which often raises topics about humanity and his real-life. Using a three-dimensional framework of Fairclough (1989; 1992a; 1992b; 1995a; and 1995b), this study critically explores the various efforts made by Olyrinson in the short story